Kerajaan Seribu Tahun Dalam Perspektif Kaum Injili - Julitinus Harefa; Meniati Hia (Jurnal Missio Cristo, 2022)
In the Millennial Era, some Christian theologians have forgotten and abandoned the doctrine of the Millennial Kingdom which in fact was inherited from the early church fathers. Even more, narrowed and sharper differences are caused by this doctrine, thus creating suspicion among the people through hypocritical Bible texts for self-justification. The presence of this scientific work aims to find out again the main points of truth contained in the Thousand Years doctrine written in God's Word. Whether the Millennium Kingdom is an event that will occur in the future or is currently taking place. In hermeneutic language, whether this Millennial Kingdom is literal (literal) or figurative (figuratively). Therefore, to restore the interest of Christian theologians regarding the attitude towards the Millennial doctrine, a comparative study of the three Millennials is needed which will be presented in the following discussion. For the approach to this study, the author uses library research methods. These efforts will provide an overview for readers to determine how to determine which one is closest to and in accordance with Bible truth. Abstrak Bahasa Indonesia Di Era-millenial beberapa teolog Kristen telah melupakan dan meninggalkan doktrin tentang Kerajaan Seribu Tahun yang notabene warisan dari para Bapa-bapa gereja mula-mula. Bahkan semakin mengerucut dan tajam perbedaan yang ditimbulkan oleh doktrin ini, sehingga menciptakan suasana mencurigai diantara umat dengan memunafikkan teks-teks Alkitab demi pembenaran diri. Kehadiran karya ilmiah ini bermaksud untuk merenungkan kembali pokok-pokok kebenaran yang terkandung dalam doktrin Kerajaan Seribu Tahun yang dituliskan dalam Firman Tuhan. Apakah Kerajaan Seribu Tahun merupakan peristiwa yang terjadi diwaktu yang akan datang atau sedang berlangsung. Dalam bahasa hermeneutiknya, apakah Kerajaan Seribu Tahun ditafsirkan secara harafiah (literal) atau Figuratif (kiasan). Oleh sebab itu, untuk mengembalikan minat para teolog Kristen terkait pengambilan sikap yang tepat pada doktin Millenial dibutuhkan studi perbandigan diantara ketiga paham Millenial yang akan dipaparkan pada pembahasan berikutnya. Untuk pendekatan pada kajian ini penulis menggunakan metode penelitian literatur. Upaya tersebut akan memberikan gambaran kepada para pembaca untuk menentukan sikap doktrin mana yang paling mendekati dan sesuai dengan kebenaran Alkitab.